Hand grip strength‐based cachexia index as a predictor of cancer cachexia and prognosis in patients with cancer. Issue 1 (29th November 2022) - Xie, Hailun; Ruan, Guotian; Wei, Lishuang; Zhang, Heyang; Ge, Yizhong; Zhang, Qi; Lin, Shiqi; Song, Mengmeng; Zhang, Xi; Liu, Xiaoyue; Li, Xiangrui; Zhang, Kangping; et al.
Abstract: Background: The cachexia index is a useful predictor for cancer cachexia and prognostic assessment. However, its use is limited because of high testing costs and complicated testing procedures. Thus, in this study, we aimed to develop a hand grip strength (HGS)‐based cancer cachexia index (H‐CXI) as a potential predictor of cancer cachexia and prognosis in patients with cancer. Methods: Here, 14 682 patients with cancer were studied, including the discovery (6592), internal validation (2820) and external validation (5270) cohorts. The H‐CXI was calculated as [HGS (kg)/height (m) 2  × serum albumin (g/L)]/neutrophil‐to‐lymphocyte ratio. The Kaplan–Meier method was used to create survival curves, and the log‐rank test was used to compare time–event relationships between groups. A Cox proportional hazard regression model was used to determine independent risk factors for overall survival (OS). Logistic regression analysis was used to assess the association of the H‐CXI with short‐term outcomes and cancer cachexia. Results: There was a significant non‐linear relationship between the H‐CXI and OS in all cohorts. Patients with a low H‐CXI had significantly lower OS than those with a high H‐CXI in the discovery cohort (6‐year survival percentage: 55.72% vs. 76.70%, log‐rank P  < 0.001), internal validation cohort (6‐year survival percentage: 55.81% vs. 76.70%, log‐rank P  < 0.001), external validation cohort (6‐year survival percentage: 56.05% vs. 75.48%, log‐rank P  < 0.001) and total cohort (6‐year survival percentage: 55.86% vs. 76.27%, log‐rank P  < 0.001). Notably, the prognostic stratification effect of the H‐CXI in patients with advanced‐stage disease was more significant than that in patients with early‐stage disease. The multivariate Cox proportional risk regression model confirmed that a low H‐CXI negatively affected the prognosis of patients with cancer in the discovery cohort [hazard ratio (HR) 0.75, 95% confidence interval (CI) 0.71–0.80, P  < 0.001], internal validation cohort (HR 0.79, 95 %CI 0.72–0.86, P  < 0.001), external validation cohort (HR 0.84, 95% CI 0.79–0.89, P  < 0.001) and total cohort (HR 0.80, 95% CI 0.77–0.83, P  < 0.001). Multivariate logistic regression models showed that a low H‐CXI was an independent risk factor predicting adverse short‐term outcomes and cancer cachexia in patients with cancer. Conclusions: The simple and practical H‐CXI is a promising predictor for cancer cachexia and prognosis in patients with cancer.